Effect of Pro-inflammatory Cytokines on Intestinal Drug Transporters in Human Enteroid Monolayers - Wang, Kai (My University, 2025)
Altered drug pharmacokinetics during inflammation or infections have been linked with elevated proinflammatory cytokines in the plasma. Although oral medication is the most common route of drug administration, data on the impact of proinflammatory cytokines on the expression and activity of intestinal drug transporters remains limited. Using a novel enteroid in vitro model, we investigated the effects of key proinflammatory cytokines (i.e., interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ) on the mRNA expression of major intestinal transporters, and the activity of intestinal P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP). Differentiated enteroid monolayers were exposed to cytokines, individually or as a cocktail, at 0.1, 1, and 10 ng/mL, encompassing their pathophysiological plasma concentrations in various inflammatory or infectious diseases. After 48 hours of exposure to the cytokine cocktail, significant concentration-dependent downregulation of P-gp, BCRP, multidrug resistance proteins (MRP) 2/3, organic solute transporter-α/β, serotonin transporter, and organic anion transporter polypeptide 2B1 was observed, along with upregulation of MRP4. Among the cytokines tested, IL-1β exhibited the most pronounced effects. Subsequent Transwell® assays showed a significant decrease in the efflux ratio of nitrofurantoin, a selective BCRP substrate, after 48 hours of incubation with 1 ng/mL of each cytokine or the 1 ng/mL cytokine cocktail. Interestingly, the efflux ratio of digoxin, a P-gp substrate, was not affected by cytokines. These findings demonstrate that proinflammatory cytokines can transcriptionally dysregulate intestinal drug transporters and downregulate the activity of intestinal BCRP in vitro, highlighting the potential impact of inflammation on oral drug pharmacokinetics and the importance of optimizing dosing regimens for patients with inflammatory conditions.
Thesis (Master's)--University of Washington, 2024
Keywords: Pharmaceutical sciences; Pharmaceutics